Drumopama girisa: A rare hyphomycete from bamboo, resolved within Xylariales through morphological and molecular data - Zhou, Yifan; Liu, Jingwen; Syed, Asad; Liu, Jian-Kui; Maharachchikumbura, Sajeewa S. N. (Phytotaxa, 2025)
During a field visit in Sichuan Province, China, an undescribed hyphomycetous fungus was discovered on decaying bamboo (Bambusoideae, Poaceae). Upon morphological comparison, the fungus was identified as Drumopama girisa, a genus classified within Ascomycota genera incertae sedis due to the lack of molecular data. Preliminary BLAST searches of the ITS region suggested its placement within Xylariomycetidae (Sordariomycetes, Ascomycota). Its position was further clarified by a thorough multi-locus phylogenetic analysis utilising the nuclear ribosomal internal transcribed spacer (ITS), the partial nuclear ribosomal large subunit rRNA (LSU), the partial second-largest subunit of RNA polymerase II (RPB2) and the partial beta-tubulin (TUB) loci. This analysis showed a close relationship to Hansfordiaceae and Coniocessiaceae within Xylariales. As a result, we propose the inclusion of Drumopama within Xylariales genera incertae sedis.